Daidzein stimulates fatty acid-induced fat deposition in C2C12 myoblast cells via the G protein-coupled receptor 30 pathway. Issue 5 (3rd October 2022) - Zhou, Chengjian; Li, Ping; Han, Meihong; Gao, Xuejun
Abstract: Fat deposition in skeletal muscle is an important aspect of improving meat quality. Isoflavones can promote animal anabolism, but whether and how they regulate muscle fat deposition remain largely unclear. In this study, we explored the role and corresponding molecular mechanism of one of the major isoflavones, daidzein, in fat deposition in C2C12 myoblast cells. In the absence of fatty acids (FAs), daidzein did not promote triglyceride synthesis and lipid droplet formation in cells but increased sterol regulatory element-binding protein 1c (SREBP-1c) expression and maturation. In the presence of FAs, daidzein enhanced FAs-induced fat deposition and the SREBP-1c signaling. Daidzein promoted FAs-induced nuclear factor κB1 (NFκB1) phosphorylation and activated the SREBP-1c signaling in a PI3K-dependent manner. G protein-coupled receptor 30 (GPR30) knockdown but not estrogen receptor α (ERα) knockdown blocked the stimulation of daidzein on the PI3K-NFκB1-SREBP-1c signaling pathway, while both knockdown did not affect the stimulation of FAs on this signaling. qRT-PCR and ChIP-qPCR further detected that daidzein stimulated NFκB1-targeted SREBP-1c transcription. Daidzein did not affect ERα expression in cells, but it stimulated GPR30 expression and cytoplasmic localization. These results reveal that daidzein promotes FAs-induced fat deposition through the GPR30 signaling in C2C12 myoblast cells.